PELATIHAN PEMBUATAN SABUN DARI MINYAK JELANTAH SEBAGAI PELUANG USAHA SANTRI PESANTREN FATAHILAH - Pusporini Pusporini; Tati Handayani; Anggi Angga Resti (LPPM Universitas Bina Bangsa, 2024)
Islamic boarding schools, known as pesantren, play a crucial role in shaping the character and skills of their students. However, to achieve self-reliance and economic empowerment, pesantren need to develop community service programs that are oriented towards entrepreneurship. This article discusses a training program conducted at Fatahilah Islamic Boarding School with the aim of teaching students about environmentally friendly soap making using used cooking oil as a raw material. The training program aims to provide knowledge and skills to students in processing used cooking oil into economically valuable products. Additionally, the training program also aims to raise awareness about the importance of managing used cooking oil waste and its negative impact on the environment. The article will cover the training methods, the topics taught, and the outcomes achieved after the training. The results of this training program are expected to provide business opportunities for students to produce and sell soap made from used cooking oil, thus increasing their income and reducing environmental pollution caused bywaste